Causes and effects of poor communication in construction projects - Rageh Gamil, Yaser Mohammed (2020)
Effective communication is an indispensable element to the successful completion of construction projects. However, maintaining a smooth and effective communication process is a challenge to construction practitioners. Many studies have been carried out on the communication in construction. Nevertheless, there is still lack of studies focusing exclusively on the identification of limited causes and effects of poor communication in the construction projects. Hence, this study is not only intended to entirely identify and assess the causes and effects of poor communication but also to establish the relationships between them. The study was conducted using mix method approaches where the qualitative approach was carried out using exploratory interviews with ten selected construction experts to gain insights on the issues of poor communication in Malaysian construction. The information gathered from interviews were analysed using thematic content analysis. In the quantitative approach, a questionnaire survey was used to collect data from 262 respondents to assess the cause and effect factors. The questionnaire was designed based on the causes and effects identified from the literature and the exploratory interview which simultaneously resulted in identifying 43 causes and 23 effects. The collected data were analysed using statistical univariate and multivariate approaches. The univariate analysis adopted average index score to rank the significance level of the factors and found five most significant causal factors which are lack of communication system and platform, improper communication channel, lack of appropriate communication medium, poor project information management, and lack of formal execution of communication. While the five most severe effects of poor communication are information overlapping, time overrun, cost overrun, dispute, and high stress in the workplace. The collected data were further used to develop a structural relationship model for the causes and effects using Smart-PLS. The model was assessed and validated for both measurement and structural components. The model addressed the relationships between causes and effects which then verified by construction experts. The structural equation model with the outcome from exploratory interviews were combined to produce a framework of poor communication causes and effects. The framework also introduced the mitigation measures of poor communication. The findings of this research are helpful to accommodate the need for construction practitioners and stakeholders to understand the most significant causes, most severe effects, and offered mitigation measures of poor communication.